Peningkatan Kesadaran dan Kewaspadaan Masyarakat terhadap Komplikasi Tuberkulosis Paru dan Ekstraparu - Adelgrit Trisia; Lia Sasmithae; Ranintha Br Surbakti; Tisha Patricia; Astrid Teresa (LP2M INSURI Ponorogo, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, including in the working area of the Pahandut Community Health Center, Palangka Raya. Local surveillance data showed a sharp increase in TB cases, from 82 in 2019 and 77 in 2020 to 249 in 2021, highlighting the need for stronger community-based interventions. This community service program aimed to improve public knowledge of pulmonary and extrapulmonary TB, strengthen the role of health cadres, and provide basic health screening. Activities included structured health education, interactive discussions, pre and post–knowledge assessments, symptom screening, blood pressure measurement, nutritional assessment, and supplementary nutrition. Participants included TB patients, high-risk groups, Posyandu cadres, and community members. Results showed improved participant knowledge, as indicated by higher post-test scores. Screening of 39 participants identified hypertension as the most common adult comorbidity and acute respiratory infections among children. Community-based education, combined with basic health screening, effectively increased TB awareness and supported early detection.